Development of Techniques for Trace Gas Detection in Breath - Langley, C; Cathryn Langley (2012)
This thesis aims to investigate the possibility of developing spectroscopic techniques for trace gas detection, with particular emphasis on their applicability to breath analysis and medical diagnostics. Whilst key breath molecules such as methane and carbon dioxide will feature throughout this work, the focus of the research is on the detection of breath acetone, a molecule strongly linked with the diabetic condition. Preliminary studies into the suitability of cavity enhanced absorption spectroscopy (CEAS) for the analysis of breath are carried out on methane, a molecule found in varying quantities in breath depending on whether the subject is a methane-producer or not. A telecommunications near-infrared semiconductor diode laser (1.6 µm) is used with an optical cavity based detection system to probe transitions within the vibrational overtone of methane. Achieving a minimum detectable sensitivity of 600 ppb, the device is used to analyse the breath of 48 volunteers, identifying approximately one in three as methane producers. Following this, a second type of laser source, the novel and widely tunable Digital Supermode Distributed Bragg Reflector (DS-DBR) laser, is characterised and the first demonstration of its use in spectroscopy documented. Particular emphasis is given to its application to CEAS and to probing the transitions of the two Fermi resonance components of the CO_2 3ν_1 + ν_3 combination bands found within the spectral range (1.56 - 1.61 µm) of the laser, providing the means to determine accurate ^{13}CO_2/^{12}CO_2 ratios for use in the urea breath test. Not all molecules exhibit narrow, well-resolved ro-vibrational transitions and the next section of the thesis focuses on the detection of molecules, such as acetone, with broad, congested absorption features which are not readily discernible using narrowband laser sources. To provide the necessary specificity for these molecules, two types of broadband source, a Superluminescent Light Emitting Diode (SLED) and a Supercontinuum source (SC), both emitting over the 1.6 - 1.7 µm region, are used in the development of a series of broadband cavity enhanced absorption (BB-CEAS) spectrometers. The three broadband absorbers investigated here, butadiene, acetone and isoprene, all exhibit overtone and combination bands in this spectral region and direct absorption measurements are taken to determine absorption cross-sections for all three molecules. The first BB-CEAS spectrometer couples the SLED device with a dispersive monochromator, attaining a minimum detectable sensitivity of 6 x 10^{-8} cm^{-1}, which is further enhanced to 1.5 x 10^{-8} cm^{-1} on replacing the monochromator with a Fourier Transform interferometer. The spectral coverage is then extended to 1.5 - 1.7 µm by coupling the first SLED with a second device, providing a demonstration of simultaneous multiple species detection. Finally, a SC source is used to provide greater power and uniform spectral intensity, resulting in an improved minimum detectable sensitivity of 5 x 10^{-9} cm^{-1}, or 200 ppb, 400 ppb and 200 ppb for butadiene, acetone and isoprene respectively. This device is then applied to acetone-enriched breath samples; the resulting spectra are fitted with a simulation to return the acetone levels present in the breath-matrix. Following this, the development of a prototype breath acetone analyser, carried out at Oxford Medical Diagnostics Ltd. (OMD), is described. To fulfill the requirements of a compact and commercially-viable device, a diode laser-based system is used, which necessitates a thorough investigation into all possible sources of absorption level change. Most notably, this includes a study into the removal and negating of interfering species, such as water vapour, and to a lesser extent, methane. A novel solution is presented, utilising a water-removal device in conjunction with molecular sieve so that each breath sample generates its own background, which has allowed breath acetone levels to be measured within an uncertainty of 200 ppb. Spectroscopic detection then moves to the mid-infrared with the demonstration of a continuous wave 8 µm quantum cascade laser, which allows the larger absorption cross-sections associated with fundamental vibrational modes to be probed. Following the laser's characterisation using methane, including a wavelength modulation spectroscopy study, the low effective laser linewidth is utilised to resolve rotational structure in low pressure samples of pure acetone. Absorption cross-sections are determined before the sensitivity of the system is enhanced for the detection of dilute concentrations of acetone using two types of multipass cells, firstly a White cell and secondly a home-built Herriott cell. This allows an acetone minimum detectable absorption of 350 ppb and 20 ppb to be attained, respectively. Following this, an optical cavity is constructed and, on treating breath samples in a water-removal device prior to analysis, breath acetone levels determined and corroborated with a mass spectrometer. <p.finally, 25="" 280="" a="" absorption="" acetone="" an="" and="" arrangement="" at="" be="" breath="" cavity="" centred="" combining="" commercially="" compact="" could="" cross-sections="" demonstrated="" detection="" detection.<="" development="" finesse="" for="" further="" imaging="" in="" is="" large="" led="" low="" nm="" of="" optical="" optimum="" p="" possible="" potential="" ppm="" preliminary="" presented.="" probing="" represent="" resolved.="" solution="" spectrograph,="" structure="" study="" the="" this="" to="" ultimately="" ultraviolet="" utilising="" viable,="" vibronic="" with=""></p.finally,>